The The Influence of AI Phenomenon on Creativity and Problem Solving Skills in Urban and Rural SMK Teacher - Anggana, Bima; Cholik, Mochamad; Anwar, Saiful; Susanti, Nuraini (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to analyze the effect of artificial intelligence (AI) phenomenon on the creativity and problem-solving skills of vocational teachers in urban and rural areas. Entering the digital age, AI has the potential to become an important instrument in vocational education, both in enhancing personalized learning and bridging the digital divide, especially between urban and rural schools. The population of this study was teachers of SMK Engineering Study Program in Surabaya (urban) and Bojonegoro (rural), with a total sample of 100 teachers, 50 teachers each from both regions. MANOVA was used to analyze the effect of AI as a predictor of creative thinking and problem solving skills, as well as the moderating effect of school environment between urban and rural areas. The results showed that AI had a significant effect on improving creativity and problem-solving ability in vocational school teachers, with notable differences between urban and rural areas. Teachers in urban schools showed greater improvement in creativity, while rural teachers were helped more in problem-solving ability with the help of AI.